Responses to Microbial Challenges by SLAMF Receptors - B.J. van Driel; Gongxian Liao; Pablo Engel; Cox Terhorst (2016)
The SLAMF Family (SLAMF) of cell surface glycoproteins is comprised of nine glycoproteins and whilst SLAMF1, 3, 5, 6, 7, 8, 9 are self-ligand receptors, SLAMF2 and SLAMF4 interact with each other. Their interactions induce signal transduction networks in trans, thereby shaping immune cell-cell communications. Collectively, these receptors modulate a wide range of functions, such as myeloid cell and lymphocyte development and, T and B cell responses to microbes and parasites. In addition, several SLAMF receptors serve as microbial sensors, which either positively or negatively modulate the function of macrophages, dendritic cells, neutrophils and NK cells in response to microbial challenges. The SLAMF receptor-microbe interactions contribute both to intracellular microbicidal activity as well as to migration of phagocytes to the site of inflammation. In this review, we describe the current knowledge on how the SLAMF receptors and their specific adapters SAP and EAT-2 regulate innate and adaptive immune responses to microbes.